HISTOLOGY AND IMMUNOHISTOCHEMISTRY OF CANINE MESENCHYMAL TUMOURS - Chandravati, T; Anjanayelly, Y; Kumar, A Ananad (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Cancer is the major cause of mortality in pet dogs and humans. Assessment of the cell kinetics is a field of interest in modern oncology and it indicates the prognosis. Out of 68 cases screened, histopathologically 19 were found to be mesenchymal tumours. Among 19 cases, fibroma 3 (15.78%), fibrosarcoma 2 (10.52%), fibromatous epulis 2 (10.52%), lipoma 2 (10.52%), osteosarcoma 2 (10.52%), hemangiopericytoma 2 (10.52%), chondrosarcoma 1 (5.26%), myxoma 1 (5.26%), leiomyoma 1 (5.26%), rhabdomyosarcoma 1 (5.26%), lymphangiosarcoma 1 (5.26%) and hemangioma 1 (5.26%). The mean number of AgNOR dots and PCNA counts in benign tumours was significantly (P<0.05) lower than malignant tumours and both indices together give good prognostic value rather than following a single.